Pertanggungjawaban Pidana Korporasi atas Pencemaran dan Perusakan Lingkungan: Studi Normatif terhadap Prinsip Strict Liability di Indonesia - Rafli Ramdani; Chandra Devaraihan Wahyudi; Sultan Novaliyana Putra (Journal of Legal, Political, and Humanistic Inquiry, 2025)
Corporations play a vital role in economic development, yet massive industrialization often negatively impacts environmental sustainability. This article examines the legal construction of corporate criminal liability in environmental crimes in Indonesia. The research focuses on the paradigm shift from "societas delinquere non potest" to recognizing corporations as subjects of criminal law, as well as analyzing the application of Law No. 32 of 2009 concerning Environmental Protection and Management (UU PPLH) and Supreme Court Regulation (PERMA) No. 13 of 2016. The research method used is normative juridical. The discussion results indicate that corporate criminal liability is absolutely necessary to provide a deterrent effect and environmental remediation. The application of the Strict Liability principle and identification theory are crucial instruments for law enforcement to prosecute corporations, not only at the field operator level but also the directing mind or corporate management.